EDUKASI DAN PEMERIKSAAN POSTUR TUBUH PADA SISWA-SISWI DI SMA NEGERI 7 DENPASAR - Novianti, I Gusti Ayu Sri Wahyuni; Paramurthi, I.A.Pascha; Prianthara, I Made Dhita; Suadnyana, Ida Ayu Astiti; Suparwati, Komang Tri Adi; Astrawan, I Putu; Jaya, I Putu Prisa; Manuaba, Ida Ayu Ratih Wulansari (Jurnal Abdi Insani, 2024)
Adolescence is a time when growth and development occur rapidly both physically, psychologically and intellectually. One of the physical changes that occur in adolescents is in the form of changes in the musculoskeletal system such as changes in body posture. Changes in posture can occur due to the use of bags and sitting positions. Adolescent knowledge about good posture is still lacking so there is a need for education and posture checks to prevent the impact of posture changes. The method used in this study is divided into three stages, namely the licensing stage, audience with the school and the implementation of activities by conducting posture checks using postural charts and reedco posture assessment. After conducting the examination then continued with the provision of education about body posture. The output of this activity is an improvement in the quality of health in adolescents who avoid musculoskeletal disorders with awareness of the importance of maintaining posture. The result of this community service activity was the number of students who participated in this activity as many as 44 people with details of men amounting to 18 people (41%), while women amounted to 26 people (59%). Students who experienced good posture as many as 37 people (84%) and students who experienced bad posture as many as 7 people (16%). Based on these results, it can be concluded that students at SMA Negeri 7 have good posture.